THE SHADOW STALLION / 2 - Blade, Adam; Dynamo (London : Orchard Books, 2018)
Welcome to Hero Academy! Join Jack and your other new classmates at this secret school, where the lessons are more exciting than Maths and PE. When a portal from the evil underground realm of Noxx is discovered beneath the school, Team Hero needs your powers. The next invasion is upon us ... There are FOUR thrilling adventures to collect in this series - don't miss out!
Keywords: Children's stories, English; English fiction; Monsters -- Juvenile fiction